2017
DOI: 10.1001/jamasurg.2016.4086
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Causes of Attrition Among Surgical Residents

Abstract: General surgery programs have relatively high attrition, with female residents more likely to leave their training programs than male residents. Residents most often relocate or switch to another specialty after the first postgraduate year owing to lifestyle-related issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
114
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(127 citation statements)
references
References 62 publications
5
114
1
3
Order By: Relevance
“…Surgeon wellness during residency and throughout a surgical career has become a priority, and this may encourage interest in surgery among students who are undecided. 133,134 One approach to ensuring wellness among surgical trainees is the restriction of duty hours, which was found in our review to have a beneficial impact on student experience of surgery and mixed impact on student pursuit of a career in surgery. 85,88,104 However, duty hour restriction is controversial, and results from prominent studies, such as the FIRST trial, illuminate the nuanced balance between duty hour policies and surgical trainee well-being.…”
Section: Discussionmentioning
confidence: 93%
“…Surgeon wellness during residency and throughout a surgical career has become a priority, and this may encourage interest in surgery among students who are undecided. 133,134 One approach to ensuring wellness among surgical trainees is the restriction of duty hours, which was found in our review to have a beneficial impact on student experience of surgery and mixed impact on student pursuit of a career in surgery. 85,88,104 However, duty hour restriction is controversial, and results from prominent studies, such as the FIRST trial, illuminate the nuanced balance between duty hour policies and surgical trainee well-being.…”
Section: Discussionmentioning
confidence: 93%
“…Trainees report stress regarding the physical risks posed by having to care for COVID-positive patients 24,25 as well as the potential impact that COVID restrictions may have on future career prospects. 26 Neurosurgical residency is demanding, 27,28 and although overall attrition rates are below average (11% between 2005 and 2010 vs. 18% for general surgery residents), 29,30 it has been noted that low operative volume and outside social stressors are associated with higher rates of burnout. 31 This situation raises concern for increased resident burnout rates during the COVID crisis.…”
Section: Resident Wellnessmentioning
confidence: 99%
“…Although there have been publications on higher attrition rates for females in surgical training programs where males are the majority in training and occupation (17), to our knowledge, no outcomes have been previously reported that similarly more males tend to drop-out from training programs where women outnumber men. This highly interesting result might by explained from social identity theory.…”
Section: Discussionmentioning
confidence: 62%
“…The attrition rate of surgical specialties in particular gains attention in the literature, particularly in the United States (22,17,6). The meta-analysis on prevalence and causes of attrition among surgical residents, performed by Zeyad Khoushhal and his colleagues sheds light on one particular nding: attrition is signi cantly higher among female trainees compared to males (25% and 15% respectively) (17). There has been a particular literature review on gender differences in the learning and teaching of surgery (9).…”
Section: Introductionmentioning
confidence: 99%